Becoming a nurse : fundamentals of professional practice for nursing - Sellman, Derek ;Snelling, Paul (London, United Kingdom : Routledge, 2017)
Becoming a Nurse will demystify what you need to know while preparing you to meet NMC standards and become a confident, practising professional. The book introduces the many subjects outside the biological which are none the less essential for both pre-registration and practising nurses. This new edition has been thoroughly updated throughout, and includes four new chapters on psychosocial concepts for nursing; sociological concepts for nursing; spiritual care; and preceptorship and transition.
1. Introduction: The State of UK Nursing -- 2. Professional Issues -- 3. Ethics -- 4. Law -- 5. Health Policy -- 6. Management and Leadership -- 7. Interprofessional Working -- 8. Evidence-based Practice -- 9. Assessment -- 10. Sociological Concepts for Nursing -- 11. Psychological Concepts for Nursing -- 12. Spiritual Care -- 13. Judgement and Decision-making -- 14. Communication and Interpersonal Skills -- 15. Public Health -- 16. Learning and Teaching -- 17. Personal and Professional Development Through Reflective Practice -- 18. Medicines Management -- 19. Preceptorship and Transition
Includes bibliographical references and index.
Keywords: NURSING